KAED 2017 : New projectors - Yaali, Syarel Azill; Ayob, Mohd Fairullazi (2017)
This paper is prepared and deliberated in Kulliyyah management meeting to report the received of new projectors. The projectors are in good condition after checked, tested and verified by the ICT staffs.